Determination of Debye temperatures and Lamb–Mössbauer factors for LnFeO3 orthoferrite perovskites (Ln = La, Nd, Sm, Eu, Gd). (16th February 2018) - Scrimshire, A; Lobera, A; Bell, A M T; Jones, A H; Sterianou, I; Forder, S D; Bingham, P A
Abstract: Lanthanide orthoferrites have wide-ranging industrial uses including solar, catalytic and electronic applications. Here a series of lanthanide orthoferrite perovskites, LnFeO3 (Ln = La; Nd; Sm; Eu; Gd), prepared through a standard stoichiometric wet ball milling route using oxide precursors, has been studied. Characterisation through x-ray diffraction and x-ray fluorescence confirmed the synthesis of phase-pure or near-pure LnFeO3 compounds. 57 Fe Mössbauer spectroscopy was performed over a temperature range of 10 K–293 K to observe hyperfine structure and to enable calculation of the recoil-free fraction and Debye temperature ( θ D ) of each orthoferrite. Debye temperatures (Ln = La 474 K; Nd 459 K; Sm 457 K; Eu 452 K; Gd 473 K) and recoil-free fractions (Ln = La 0.827; Nd 0.817; Sm 0.816; Eu 0.812; Gd 0.826) were approximated through minimising the difference in the temperature dependent experimental centre shift and theoretical isomer shift, by allowing the Debye temperature and isomer shift values to vary. This method of minimising the difference between theoretical and actual values yields Debye temperatures consistent with results from other studies determined through thermal analysis methods. This displays the ability of variable-temperature Mössbauer spectroscopy to approximate Debye temperatures and recoil-free fractions, whilst observing temperature induced transitions over the temperature range observed. X-ray diffraction and Rietveld refinement show an inverse relationship between FeO6 octahedral volume and approximated Debye temperatures. Raman spectroscopy show an increase in the band positions attributed to soft modes of Ag symmetry, Ag (3) and Ag (5) from La to GdFeO3 corresponding to octahedral rotations and tilts in the [0 1 0] and [1 0 1] planes respectively.